Genome-guided purification and characterization of polymyxin A1 from Paenibacillus thiaminolyticus SY20: A rarely explored member of polymyxins - Wu, Ya-ping; Liu, Dong-mei; Liang, Ming-hua; Huang, Yan-yan; Lin, Jin; Xiao, Lan-fang (Frontiers in Microbiology, 2022)
Polymyxin A1 was a rarely investigated member in the polymyxins family produced by Bacillus aerosporus. As a cyclic non-ribosomal lipopeptide, it was purified from Paenibacillus thiaminolyticus for the first time. The producing strain SY20 was screened from Chinese natural fermented bamboo shoots and identified as P. thiaminolyticus SY20 using 16S rRNA homology along with whole genome sequencing. The optimum incubation time was 32 h by the growth kinetics of antimicrobial agent production. The proteinaceous nature of antimicrobial agents was characterized according to the physicochemical properties of the cell-free supernatant. Subsequently, the active antimicrobial agent was purified from the supernatant using ammonium sulfate–graded precipitation, ion-exchange chromatography, and C18-H chromatography. The active agent was identified as polymyxin A1 with a molecular weight 1156.7 Da and antimicrobial activity mainly against Gram-negative bacteria. The molecular structure, a cyclic heptapeptide and a tripeptide side chain acylated by a fatty acid at the amino terminus, was elucidated using the combination of liquid chromatography-tandem mass spectrometry (LC-MS/MS), matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS), amino acid analysis, and whole genome mining tool. Meanwhile, the biosynthetic gene cluster of polymyxin A1 including five open reading frames (ORFs) was demonstrated in the genome. The compound should be further explored for its efficacy and toxicity in vivo to develop its application.